COMPARATIVE ANALYSIS OF INTRINSIC MOTIVATION LEVEL OF ATHLETES BETWEEN 16 TO 18 YEARS OF AGE WHO ARE PARTICIPANTS OF TEAM AND INDIVIDUAL SPORTS WITH DIFFERENT LEVELS OF EXPERIENCE. (Fiep Bulletin - online, 2014)
The purpose of this study was to identify the intrinsic motivation level in experience levels, and individual and team sports athletes. The sample was composed by 448 athletes, in the age ranging from 16 to 18 years old, involved in: indoor football, team handball, volley-ball, karate, swimming, judo and track and field. The data were collected using the “Psychometrics Properties of Intrinsic Motivation Inventory for a Competitive Sports Settings” (McAULEY, DUNCAN and TAMMEN, 1989), using a stratified sample system, from 10% of the population. The data analysis was conducted using multifactor analysis of variance (ANOVA), in a predictive level of p
Keywords: intrinsic motivation; individual and team sports; experience level